1999
DOI: 10.2337/diacare.22.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes and ethnic differences in cardiovascular risk factors. The 1992 Singapore National Health Survey.

Abstract: Prevalence of diabetes was high across all three ethnic groups. Ethnic differences in prevalence of diabetes, insulin resistance, central obesity, hypertension, smoking, and lipid profile could explain the differential coronary heart disease rates in the three major ethnic groups in Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
133
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(150 citation statements)
references
References 0 publications
11
133
6
Order By: Relevance
“…The population mean of BMI for Thai adults was relatively similar to those of some other countries in Asia such as Hong Kong, 15 Chinese 16 and Singapore. 17 But for WC in the present study, Thai men and women aged X35 years had a similar distribution of WC whereas in other countries, men usually has a higher WC compared to women. [15][16][17] The results of the present study suggested that Thai population, similar to Chinese population, exhibited a lower BMI and WC distribution for cardiovascular risk factors Abbreviations: BMI, body mass index; HDL-C, high-density lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; TC, total cholesterol; TG, triglyceride; WC, waist circumference.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The population mean of BMI for Thai adults was relatively similar to those of some other countries in Asia such as Hong Kong, 15 Chinese 16 and Singapore. 17 But for WC in the present study, Thai men and women aged X35 years had a similar distribution of WC whereas in other countries, men usually has a higher WC compared to women. [15][16][17] The results of the present study suggested that Thai population, similar to Chinese population, exhibited a lower BMI and WC distribution for cardiovascular risk factors Abbreviations: BMI, body mass index; HDL-C, high-density lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; TC, total cholesterol; TG, triglyceride; WC, waist circumference.…”
Section: Discussioncontrasting
confidence: 60%
“…17 But for WC in the present study, Thai men and women aged X35 years had a similar distribution of WC whereas in other countries, men usually has a higher WC compared to women. [15][16][17] The results of the present study suggested that Thai population, similar to Chinese population, exhibited a lower BMI and WC distribution for cardiovascular risk factors Abbreviations: BMI, body mass index; HDL-C, high-density lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; TC, total cholesterol; TG, triglyceride; WC, waist circumference. Dyslipidemia is defined as any of the following: TC X6.2 mmol/l; LDL-C X4.1 mmol/l; HDL-C o0.9 mmol/l for men or o1.03 mmol/l for women; TG X2.3 mmol/l, X2risk factors is defined as the presence of any two risk factors of hypertension, dyslipidemia, or diabetes, All prevalence adjusted for smoking and physical inactivity.…”
Section: Discussioncontrasting
confidence: 60%
“…15 In the Singapore Prospective Study Program (SP2), the recruitment rate in 2004-2007 was 64%. Participants were recruited from the 1992 26 and 1998 27 Singapore National Health Surveys; adjusting for the 68% response rate of these surveys yields a cumulative response rate of 43%, which is comparable with the survey estimate.…”
Section: Resultsmentioning
confidence: 57%
“…Several published biobank studies carried out in the United Kingdom, 18,19 United States, [20][21][22][23][24] Iceland, 25 and Singapore 26,27 had data on factual participation rates. In Sweden, we obtained participation data from a biobank maintained by the department of Endocrine Oncology, Uppsala University Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The methodologies of these studies have been described in detail elsewhere. [22][23][24] These studies consist of a random sample of individuals living in Singapore. Informed written consent was obtained from participants of all three studies.…”
Section: Participantsmentioning
confidence: 99%